The italian national genomic strategy: current status, challenges, and future perspectives in clinical practice and public health - Francesco Andrea Causio; Sara Farina; Alessandra Maio; Flavia Beccia; Luigi Russo; Valentina Baccolini; Matteo Chiara; Americo Cicchetti; Gualtiero I. Colombo; Giovanni Comandé; Domenico Coviello; Ruggero De Maria; et al. (Journal of Community Genetics, 2025)
This article presents the outcomes of a national initiative aimed at developing a technical document to support the future Italian National Genomic Strategy, carried out from 2021 to 2024 through the collaboration of 14 research institutions. The project was designed to align with major European genomic initiatives, particularly the “1 + Million Genomes” (1 + MG) Declaration and its supporting programs, including Beyond 1 Million Genomes (B1 + MG), the Genomic Data Infrastructure (GDI), and Genome of Europe (GoE). The initiative was structured around 12 National Mirror Groups (NMGs), each addressing a specific domain such as clinical implementation, ethical and legal issues, data governance, health economics, and public engagement. Through expert consensus and coordinated activities, the project produced a comprehensive technical document outlining seven strategic lines and related intervention areas. These include the integration of genomic testing into clinical practice, development of specialized genomic centers, creation of a national genomic data infrastructure, professional training, and public education. The proposed strategy emphasizes equitable access to genomic medicine, the use of health technology assessment to evaluate new technologies, and the importance of citizen engagement and literacy. By fostering collaboration among institutions, healthcare professionals, and the public, the final goal is to position Italy as a leader in genomic medicine and ensure the responsible, effective, and ethical use of genomics in public health and clinical care.

Lawn management promoting tall herbs, flowering species and urban park attributes enhance insect biodiversity in urban green areas - Paolo Biella; Sara Borghesan; Beatrice Colombo; Andrea Galimberti; Lorenzo Guzzetti; Davide Maggioni; Emiliano Pioltelli; Fausto Ramazzotti; Rosa Ranalli; Nicola Tommasi; Massimo Labra (Urban Forestry & Urban Greening, 2025)

Health impact of policies to reduce agriculture-related air pollutants in the UK: The relative contribution of change in PM2.5 exposure and diets to morbidity and mortality - Silvia Pastorino; Ai Milojevic; Rosemary Green; Rachel Beck; Edward Carnell; Patricia Eustachio Colombo; Tom Misselbrook; Mark Miller; Stefan Reis; Sam Tomlinson; Massimo Vieno; James Milner (Environmental Research, 2024)

Clinical efficacy of a parasiticide formulation containing eprinomectin, esafoxolaner and praziquantel (NexGard® Combo) in the treatment of natural feline aelurostrongylosis and troglostrongylosis - Angela Di Cesare; Fabrizia Veronesi; Paolo Emidio Crisi; Mariasole Colombo; Simone Morelli; Massimo Vignoli; Giulia Rigamonti; Raffaella Iorio; Eric Tielemans; Frederic Beugnet; Camille Gamblin; Donato Traversa (Veterinary Parasitology, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

2D and 3D numerical models to evaluate trabecular bone damage - Federica Buccino; Chiara Colombo; Daniel Hernando Lozano Duarte; Luca Rinaudo; Fabio Massimo Ulivieri; Laura Maria Vergani (Medical & Biological Engineering & Computing, 2021)
The comprehension of trabecular bone damage processes could be a crucial hint for understanding how bone damage starts and propagates. Currently, different approaches to bone damage identification could be followed. Clinical approaches start from dual X-ray absorptiometry (DXA) technique that can evaluate bone mineral density (BMD), an indirect indicator of fracture risk. DXA is, in fact, a two-dimensional technology, and BMD alone is not able to predict the effective risk of fractures. First attempts in overcoming this issue have been performed with finite element (FE) methods, combined with the use of three-dimensional high-resolution micro-computed tomographic images. The purpose of this work is to evaluate damage initiation and propagation in trabecular vertebral porcine samples using 2D linear-elastic FE models from DXA images and 3D linear FE models from micro-CT images. Results show that computed values of strains with 2D and 3D approaches (e.g., the minimum principal strain) are of the same order of magnitude. 2D DXA-based models still remain a powerful tool for a preliminary screening of trabecular regions that are prone to fracture, while from 3D micro-CT-based models, it is possible to reach details that permit the localization of the most strained trabecula. Graphical abstract

The hidden interplay between sex and COVID-19 mortality: the role of cardiovascular calcification - Alberto Cereda; Marco Toselli; Anna Palmisano; Davide Vignale; Riccardo Leone; Valeria Nicoletti; Chiara Gnasso; Antonio Mangieri; Arif Khokhar; Gianluca Campo; Alessandra Scoccia; Matteo Bertini; et al. (GeroScience, 2021)
Recent clinical and demographical studies on COVID-19 patients have demonstrated that men experience worse outcomes than women. However, in most cases, the data were not stratified according to gender, limiting the understanding of the real impact of gender on outcomes. This study aimed to evaluate the disaggregated in-hospital outcomes and explore the possible interactions between gender and cardiovascular calcifications. Data was derived from the sCORE-COVID-19 registry, an Italian multicentre registry that enrolled COVID-19 patients who had undergone a chest computer tomography scan on admission. A total of 1683 hospitalized patients (mean age 67±14 years) were included. Men had a higher prevalence of cardiovascular comorbidities, a higher pneumonia extension, more coronary calcifications (63% vs.50.9%, p<0.001), and a higher coronary calcium score (391±847 vs. 171±479 mm 3 , p <0.001). Men experienced a significantly higher mortality rate (24.4% vs. 17%, p =0.001), but the death event tended to occur earlier in women (15±7 vs. 8±7 days, p = 0.07). Non-survivors had a higher coronary, thoracic aorta, and aortic valve calcium score. Female sex, a known independent predictor of a favorable outcome in SARS-CoV2 infection, was not protective in women with a coronary calcification volume greater than 100 mm 3 . There were significant differences in cardiovascular comorbidities and vascular calcifications between men and women with SARS-CoV2 pneumonia. The differences in outcomes can be at least partially explained by the different cardiovascular profiles. However, women with poor outcomes had the same coronary calcific burden as men. The presumed favorable female sex bias in COVID-19 must therefore be reviewed in the context of comorbidities, especially cardiovascular ones.

Global approaches to assessing, monitoring, mapping, and remedying soil pollution - Natalia Rodríguez Eugenio; Ravi Naidu; Claudio Massimo Colombo (Environmental Monitoring and Assessment, 2020)

Deficits in memory and visuospatial learning correlate with regional hippocampal atrophy in MS - Giulia Longoni; Maria A. Rocca; Elisabetta Pagani; Gianna C. Riccitelli; Bruno Colombo; Mariaemma Rodegher; Andrea Falini; Giancarlo Comi; Massimo Filippi (Brain Structure and Function, 2015)

ER Reorganization is Remarkably Induced in COS-7 Cells Accumulating Transmembrane Protein Receptors Not Competent for Export from the Endoplasmic Reticulum - Massimo D’Agostino; Arianna Crespi; Elena Polishchuk; Serena Generoso; Gianluca Martire; Sara Francesca Colombo; Stefano Bonatti (The Journal of Membrane Biology, 2014)

Validation of FreeSurfer-Estimated Brain Cortical Thickness: Comparison with Histologic Measurements - Francesco Cardinale; Giuseppa Chinnici; Manuela Bramerio; Roberto Mai; Ivana Sartori; Massimo Cossu; Giorgio Lo Russo; Laura Castana; Nadia Colombo; Chiara Caborni; Elena De Momi; Giancarlo Ferrigno (Neuroinformatics, 2014)

Hepatocellular carcinoma in chronic hepatitis C: from bench to bedside - Alessio Aghemo; Massimo Colombo (Seminars in Immunopathology, 2013)

Therapeutic Paint of Cidofovir/Sucralfate Gel Combination Topically Administered by Spraying for Treatment of orf virus Infections - Fabio Sonvico; Gaia Colombo; Laura Gallina; Fabrizio Bortolotti; Alessandra Rossi; Colin J. McInnes; Gina Massimo; Paolo Colombo; Alessandra Scagliarini (The AAPS Journal, 2009)

The effect of residual water on antacid properties of sucralfate gel dried by microwaves - Alessandro Gainotti; Elena Losi; Paolo Colombo; Patrizia Santi; Fabio Sonvico; Daniela Baroni; Gina Massimo; Gaia Colombo; Pasquale Del Gaudio (AAPS PharmSciTech, 2006)

Coumaphos Distribution in the Hive Ecosystem: Case Study for Modeling Applications - Paolo Tremolada; Iris Bernardinelli; Mario Colombo; Massimo Spreafico; Marco Vighi (Ecotoxicology, 2004)

The suitability of disintegrating force kinetics for studying the effect of manufacturing parameters on spironolactone tablet properties - Gina Massimo; Patrizia Santi; Gaia Colombo; Sara Nicoli; Franca Zani; Paolo Colombo; Ruggero Bettini (AAPS PharmSciTech, 2003)

Effect of drying methods on retention of moist sucralfate gel properties - L. Maggi; P. L. Catellani; E. Fisicaro; P. Santi; F. Zani; G. Massimo; P. Colombo (AAPS PharmSciTech, 2000)